2002
DOI: 10.1556/aagr.50.2002.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping faba bean with some legume crops for control of Orobanche crenata

Abstract: Experiments involving the intercropping faba bean with each of lupin, fenugreek and Egyptian clover as well as growing faba bean alone were carried out at Assiut University on a farm naturally infested with Orobanche in two seasons. The major objective of the study was to investigate the effect of different intercropping combinations with faba bean on the infestation with Orobanche. The results obtained revealed that intercropping faba bean with each of lupin, fenugreek and Egyptian clover markedly reduced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 1 publication
6
14
0
Order By: Relevance
“…2). This is in agreement with published reports on reduction broomrape infection of faba bean (Vicia faba) intercropped with fenugreek under field conditions (Bakheit et al, 2002;Kharrat and Halila, 2005).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2). This is in agreement with published reports on reduction broomrape infection of faba bean (Vicia faba) intercropped with fenugreek under field conditions (Bakheit et al, 2002;Kharrat and Halila, 2005).…”
Section: Resultssupporting
confidence: 93%
“…An alternative approach is intercropping of susceptible host with inhibitory crops (Fernández-Aparicio et al, 2006b). In line with this approach, some studies have been done and suggested that intercropping fenugreek with faba bean (Vicia faba L.) can reduce crenate broomrape infection (Bakheit et al, 2002;Fernández-Aparicio et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…, 2005). On the other hand, fenugreek roots have been suggested to inhibit O. crenata germination, resulting in reduced infection of legumes when intercropped with the plant (Bakheit et al. , 2002; Evidente et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported as having potential as a trap crop of O. ramosa, as it induces O. ramosa seed germination but is little infected by the parasite (Abebe et al, 2005). On the other hand, fenugreek roots have been suggested to inhibit O. crenata germination, resulting in reduced infection of legumes when intercropped with the plant (Bakheit et al, 2002;Evidente et al, 2007;Ferna´ndez-Aparicio et al, 2007). The goal of this study was to determine the effects of fenugreek root exudate on the germination of O. crenata, O. ramosa and O. foetida seeds, and to isolate and determine the activity of fractions recoverable by chromatography and other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Al-Menoufi et al (1996) indicated the possibility of intercropping lupin, coriander and Brassica rapa with faba bean or tomato to reduce Orobanche infestation. Bakheit et al (2002), found a similar trend when fenugreek, lupin and Egyptian clover, were intercropped with the resistant faba bean cultivar Giza 429, causing a reduction of O.crenata spikes that amounted to 58%, 56%, and 68% compared to the control, respectively. Abu-Shall and Ragheb (2014), reported a reduction in O.crenata emerged spikes amounting to 79% when the cultivar Aquadulce was intercropped with radish, 63% with celery and berseem clover, 59% with flax, 52% with fenugreek and 42% with garlic.…”
Section: Introductionmentioning
confidence: 60%